2009
DOI: 10.1021/jm900555u
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel, Selective, and Stable Inhibitors of Class II Histone Deacetylases. Validation Studies of the Inhibition of the Enzymatic Activity of HDAC4 by Small Molecules as a Novel Approach for Cancer Therapy

Abstract: 5-Aryl-2-(trifluoroacetyl)thiophenes were identified as a new series of class II HDAC inhibitors (HDACi). Further development of this new series led to compounds such as 6h, a potent inhibitor of HDAC4 and HDAC6 (HDAC4 WT IC(50) = 310 nM, HDAC6 IC(50) = 70 nM) that displays 40-fold selectivity over HDAC1 and improved stability in HCT116 cancer cells (t(1/2) = 11 h). Compounds 6h and 2 show inhibition of alpha-tubulin deacetylation in HCT116 cells at 1 microM concentration and antiproliferation effects only at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…This structurally unique small molecule inhibitor showed preferential inhibition of HDAC8 (IC 50 =90 nM) vs all other HDACs (>18-fold selectivity over HDACs 1, 2, and 6). In 2008, Jones et al [97,98] reported a series of 5-(trifluoroacetyl)thiophene-2-carboxamides as novel, potent, and selective class II HDACi exemplified by compound 9 (HDAC4 IC 50 =320 nM; HDAC6 IC 50 =310 nM). X-ray crystal structures of HDAC4 with compound 9 demonstrate these compounds are active site inhibitors and bind in their hydrated form.…”
Section: Other Zinc-binding Motifsmentioning
confidence: 99%
“…This structurally unique small molecule inhibitor showed preferential inhibition of HDAC8 (IC 50 =90 nM) vs all other HDACs (>18-fold selectivity over HDACs 1, 2, and 6). In 2008, Jones et al [97,98] reported a series of 5-(trifluoroacetyl)thiophene-2-carboxamides as novel, potent, and selective class II HDACi exemplified by compound 9 (HDAC4 IC 50 =320 nM; HDAC6 IC 50 =310 nM). X-ray crystal structures of HDAC4 with compound 9 demonstrate these compounds are active site inhibitors and bind in their hydrated form.…”
Section: Other Zinc-binding Motifsmentioning
confidence: 99%
“…binding domain is substituted by a trifluoromethyloxadiazolyl group (TFMO) [26] that highly resembles the trifluoromethylketone (TFMK) adopted by Bottomley and colleagues in their biochemical study of the ZBD [31]. The ring structure of the TFMO group increases its stability with respect to the highly unstable TFMK series of compounds [79]. Moreover, this TFMO moiety, differently from hydroxamate, acts as a non-chelating metal binding group, which interacts with the ''catalytic'' Zn 2?…”
Section: Class Iia Inhibitorsmentioning
confidence: 99%
“…A similar thiophene 11 with a trifluoromethyl ketone group was inactive on HDAC6 at the highest concentration tested. [20] This indicates that very subtle differences in the interplay of the different structural elements govern HDAC selectivity in somewhat similar molecules, which warrants further exploration. Key interactions for HDAC6 affinity of 1 could be identified already ( Figure 1) and can be used to guide further synthetic optimization.…”
Section: Wwwchemmedchemorgmentioning
confidence: 99%